Potassium canrenoate compounding for administration via enteral feeding tubes: a physical and microbiological stability study. Issue Volume 25:Issue e2(2018) (5th August 2017) - Logrippo, Serena; Sestili, Matteo; Ganzetti, Roberta; Bonacucina, Giulia; Marziali, Antonella; Fattoretti, Patrizia; Busco, Silvia; Caraffa, Alessandro; Polidori, Carlo; Palmieri, Giovanni Filippo
Abstract : Background: Swallowing difficulties are arising in an increasing number of patients, especially in elderly people. When deglutition ability is completely compromised, enteral administration of a drug via feeding tubes is used. Licensed pharmacists have to compound the original solid forms to enable this drug therapy. Objectives: To evaluate the possibility of compounding original commercial tablets to produce a liquid formulation suitable for administering via a feeding tube. Methods: Two liquid formulations containing potassium canrenoate 5 mg/mL were prepared: a standard solution obtained by solubilising raw material and an extemporaneous preparation obtained by dissolving film-coated 100 mg tablets. Spectrophotometric determinations (UV range) of the drug established chemical stability of the analyte up to 60 days. Samples were tested for microbial growth. Gravimetric quantifications of liquid formulations were used to check any weight loss during the different steps before enteral administration. Results: UV data confirmed the chemical stability of potassium canrenoate up to 60 days. Samples showed no microbial growth. A higher weight loss was recorded in extemporaneous preparations than in the standard solution (10.7% vs 7.6%) according to the gravimetric quantification. Conclusion: It is possible to compound the original tablets into a liquid formulation suitable for administration via a feeding tube.